PEMANFAATAN SELULOSA TUMBUHAN ECENG GONDOK (Eichornia crassipes ) DENGAN PENAMBAHAN GLISEROL DAN KARAGENAN PADA PEMBUATAN EDIBLE FILM - Budiantoro, Iqro’; Ali, Akhyar; Yusmarini, Yusmarini (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
The study was aimed to get the best treatment ratio of utilization water hyacinth cellulose as a base material in the manufacture of edible film with the addition of glycerol and carrageenan. The study was conducted using Completely Randomized Design (RAL) consisting of six treatments with each treatment repeated three times. The treatments in this study were E0 (without addition of water hyacinth cellulose), E1 (percentage of 1% water hyacinth cellulose), E2 (percentage of water hyacinth cellulose 2%), E3 (percentage of water hyacinth cellulose 3%), E4 (percentage of water hyacinth cellulose 4%) and E5 (percentage of 5% water hyacinth cellulose). The observed parameters were thickness (mm), transparency, water vapor transmission rate (g/hour.m2), water resistance (%), tensile strength (MPa) and percent elongation (%). The data obtained were tested statistically using ANOVA. If F arithmetic was greater than F table then analysis will be continued with DNMRT test at 5% level. The result showed that the percentage of addition of water hyacinth cellulose powder had significant effect on thickness, transparency, vapor transmission rate, water resistance, tensile strength and percent elongation. The best treatment is treatment with percentage of 1% cellulose powder added with thickness value     0,139 mm, transparency 1,029, vapor transmission 1,323 g / hour.m2, water resistance 5,829%, tensile strength 6,104 MPa and percent elongation 23,885%. Keywords: Cellulose, water hyacinth, glycerol, carrageenan.